Danish Digital Design and the Gradual Erosion of Technology Neutral Administrative Law - Michael Gøtze (Central European Public Administration Review)
Purpose: Holding pole position in the digital race, Denmark is an EU member state that not only has inherent incentives for self-scrutiny to avoid digital hybris but also serves as an inspiration for other countries aiming to move into the fast lane of digital designs. In the wake of strong digitization within Danish public administration, a fundamental legal question arises: does digitization change the core content of general administrative law? Against this backdrop, the purpose of this article is to examine the existing Danish doctrine of technology neutral law, which asserts that digitization does not interfere with substantive law and does not negatively affect citizens’ rights. Approach: The article establishes a discussion based on relevant sources of law such as the Danish political agreement on digitally ready legislation, examples of sectoral legislation (parts of Danish tax law), and the practices and recommendations of the influential Danish Parliamentary Ombudsman. Findings: The article’s conceptual finding is that the doctrine of technology neutral law is not fully justified. In 2024, Danish legislation is increasingly designed to be digitally compatible from the very beginning, which is a significant shift. This new legislative concept has been named digitally ready legislation (digital by design), denoting legislation that is ready and “pre-cooked” in its phrasing and concepts to be transformed into subsequent digital solutions. Another finding of the article is that the proactive digital focus of the new regulation (acts and general administrative regulation) may come at a cost, potentially reducing the flexibility and adaptive quality of regulatory templates that are crucial to the rule of law. Practical Implications: The article aims at identifying the practical – and possibly negative – implications inherent in digitally ready legislation. To this end, it explores various rule-of-law and legal certainty scenarios. A key challenge is to strike a fair balance between regulation with an open-ended and discretionary design and close-ended rule-based frameworks relying on objective criteria. While pushing the agenda of digitally ready legislation brings clear benefits for administrative efficiency and promotes equal treatment across sectors, and although Denmark consistently ranks in the top end of the digital class in Europe, the ongoing digital reform also presents certain issues. Arguably, the reform may represent a drawback towards a more simplified legal geometry that does not fully accommodate the diversity of citizens and enterprises subject to Danish law. As the notion of technology neutral administrative law is gradually eroding, this article calls for a more reality-based discussion about the level of citizens’ rights vis-à-vis public authorities. Administrative law itself may need to be re-designed and made more rule-of-law ready. Value: The article offers a reflective, rule-of-law-based commentary on the ongoing strong political push for digitally ready Danish legislation.